Iatrogenic Cerebral Amyloid Angiopathy After Childhood Brain Surgery: Novel Findings of MRI and CT - Fumine Tanaka; Maki Umino; Megumi Matsukawa; Seiya Kishi; Ryota Kogue; Norikazu Kawada; Ken Kagawa; Takaya Utsunomiya; Hiroyuki Kajikawa; Hidehiro Ishikawa; Yuichiro Ii; Akihiro Shindo; et al. (Neurology International)
Background/Objectives: A subtype of cerebral amyloid angiopathy (CAA), iatrogenic CAA (iCAA), has been increasingly reported. iCAA occurs primarily in patients who underwent surgery during childhood and is caused by the prion-like propagation of amyloid beta. This subtype of CAA tends to develop at a younger age than age-related CAA, usually before the age of 55. After a latency period of 20–40 years following surgery, it manifests as lobar intracerebral hemorrhage (ICH), cognitive impairment, or transient focal neurological episodes. Between 2023 and 2024, we observed four cases of possible iCAA, all of which had a history of neurosurgery during childhood. Case presentation: MRI findings for all cases revealed multiple lobar microbleeds. Two cases also showed cortical superficial siderosis and lobar ICH. Notably, contrast-enhanced 3D FLAIR demonstrated sulcal enhancement in two cases, and CT demonstrated cortical calcification in the bilateral posterior lobes in one case. Conclusions: Sulcal enhancement on contrast-enhanced 3D FLAIR and cortical calcification in the bilateral posterior lobes on CT may suggest advanced CAA in the present cases.